Exposure to warfare and demoralization: acute stress symptoms and disengaged coping as mediators - Svetlana Baziliansky; Wafaa Sowan (European Journal of Psychotraumatology)
Background: Demoralization in the face of adversity is a common existential state. However, it has not been examined in reaction to warfare, and the mediators between the extent of exposure to war and demoralization in this context are also unknown.Objective: This study explored the associations of indirect exposure to war, acute stress symptoms, disengaged coping, and demoralization. Additionally, it examined the serial mediation of acute stress symptoms and disengaged coping in the relationship between indirect exposure to war and demoralization.Method: The survey was conducted 4 weeks after the 7 October war broke out and included 393 Israeli citizens (women and men, Jews and Arabs) indirectly affected by the threatening situation in Israel. Questionnaires measured acute stress symptoms, disengaged coping, and demoralization. War-related exposure and demographic data were collected.Results: The analysis revealed that the higher the indirect exposure to war, the higher the acute stress symptoms, use of disengaged coping, and demoralization. Additionally, individuals with acute stress disorder had higher demoralization. The serial mediation model showed partial mediation: acute stress symptoms and the use of disengaged coping mediated the relationships between indirect exposure to war and demoralization (although the direct association between the extent of exposure and demoralization remained significant).Conclusions: In the face of traumatic events, such as warfare, professionals should identify individuals with high levels of acute stress symptoms and provide help to reduce the use of disengaged coping and long-term negative consequences such as demoralization.